2016
DOI: 10.1002/aic.15358
|View full text |Cite
|
Sign up to set email alerts
|

Discrete particle modeling of lateral jets into a packed bed and micromechanical analysis of the stability of raceways

Abstract: Gas jets are often used to promote heat and mass transfer by forming raceways or circulating regions in a packed bed. Such an operation is common and critical in many processes. Multiple raceways can interact and be affected by the formation of different flow zones. This work develops a multiscale model to examine the formation and the stability of raceways and the underlying micromechanics. Four states are observed in the fluidized flow regime. More fundamentally, a critical bed width for the observation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A mathematical model to analyze the particle motion and the fluid flow in raceway used in this study has fundamentally same structure as the previous analyses. 45,46,[50][51][52][53][54][55] In other word, the particle tracking method and the computational fluid dynamics are combined. Details of the model are explained in the following sections.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A mathematical model to analyze the particle motion and the fluid flow in raceway used in this study has fundamentally same structure as the previous analyses. 45,46,[50][51][52][53][54][55] In other word, the particle tracking method and the computational fluid dynamics are combined. Details of the model are explained in the following sections.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…45) As used in some combustion analyses, 45,46) the combination of the particle tracking method for the particle motion and techniques of computational fluid dynamics have been applied to the analysis of the raceway behaviors. [50][51][52][53][54][55] Additionally, the particle tracking techniques including irregular particle shape were also applied to the raceway analyses. 56,57) These approaches successfully reproduced the formation of the cavity in the packed bed, the particle circulation motion and the gas flow pattern and clarified the effect of particle shape on the motion and heat transfer characteristics in and around the raceway.…”
Section: Introductionmentioning
confidence: 99%
“…Hilton et al demonstrated that particle shape is crucial to the structure and the dynamics of circulation regions in their CFD‐DEM simulation of lateral injection of high‐speed gas into a packed bed of different shaped particles. Recently, Hou et al used a CFD‐DEM model to study the raceway behaviors as a result of two lateral jets into a packed bed and found that with increasing superficial gas velocity, a raceway can form only when the bed width is large enough. Generally, the above studies considered the lower part of BF or a box‐shaped packed bed at a small scale.…”
Section: Modeling and Simulation Of Different Bf Regionsmentioning
confidence: 99%
“…Shen et al [14,15] established a series CFD models to study the coal combustion in raceway zone. Recently, the coupled CFD-DEM model was also developed to the particles and gas-flow in the raceway in blast furnace [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%